Reliability of ultrasonography to detect inflammatory lesions and structural damage in juvenile idiopathic arthritis - Ventura Ríos, Lucio; Faugier, Enrique; Barzola, Laura; De la Cruz Becerra, L. B.; Sánchez Bringas, Guadalupe; Rodríguez García, Andrés; Maldonado, Rocío; Roth, Johannes; Hernández Díaz, Cristina (University of Chicago, 2018)
Background Musculoskeletal Ultrasonography (MSUS) is an important tool for the clinical assessment in Juvenile Idiopathic Arthritis (JIA). The objective of this study was to evaluate the reliability of MSUS to detect elementary lesions: synovitis, tenosynovitis, cartilage damage and bone erosions in the wrist and metacarpal (MCP) joints of patients with JIA.